2020
DOI: 10.2337/dc20-1402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dapagliflozin in DAPA-HF According to Background Glucose-Lowering Therapy

Abstract: Objective: To determine whether the benefits of dapagliflozin in patients with heart failure and reduced ejection fraction (HFrEF) and type 2 diabetes in DAPA-HF varied by background glucose-lowering therapy (GLT). Research design and methods: We examined the effect of study treatment by the use or not of GLT, and by GLT classes and combinations. The primary outcome was a composite of worsening HF (hospitalization or urgent visit requiring intravenous therapy) or cardiovascular death. Results: In the 2139 type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…The characteristics of included studies are summarized in Table 1. Four trials were cardiovascular outcome trials conducted in people with T2DM at high cardiovascular risk: EMPA‐REG OUTCOME (n = 7020), the CANVAS program (n = 10142), DECLARE‐TIMI 58 (17160), and VERTIS‐CV (8246); 10,11,14,16 one (CREDENCE, n = 4401) was a kidney outcome trial in people with T2DM and chronic kidney disease 15 and one was a heart failure trial in people with heart failure with reduced ejection fraction, irrespective of diabetes status (DAPA‐HF, n = 4744) 12 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of included studies are summarized in Table 1. Four trials were cardiovascular outcome trials conducted in people with T2DM at high cardiovascular risk: EMPA‐REG OUTCOME (n = 7020), the CANVAS program (n = 10142), DECLARE‐TIMI 58 (17160), and VERTIS‐CV (8246); 10,11,14,16 one (CREDENCE, n = 4401) was a kidney outcome trial in people with T2DM and chronic kidney disease 15 and one was a heart failure trial in people with heart failure with reduced ejection fraction, irrespective of diabetes status (DAPA‐HF, n = 4744) 12 …”
Section: Resultsmentioning
confidence: 99%
“…This meta‐analysis included event‐driven, randomized, placebo‐controlled SGLT2 inhibitor cardiovascular or kidney outcome trials that reported at least one cardiovascular, kidney or mortality outcome by baseline metformin use. Treatment effects by baseline metformin use were obtained from published reports 10–13 . For eligible trials of SGLT2 inhibitors that recruited participants with and without T2DM, we included data only from participants with T2DM.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 2,139 participants with concomitant T2D in that trial, 1596 (74.6%) had been taking background glucose-lowering agents, with 1020 (47.7%) treated at least with metformin [ 38 ]. The beneficial impact of dapagliflozin on composite clinical events (worsening HF or cardiovascular death) was consistent across these background medications for T2D [ 39 ]. The present study showed that the effects of canagliflozin treatment on the HF-related parameters examined were also unaffected by baseline use of metformin treatment, although it is important to note that the baseline prescription rate of metformin was low in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there was direct evidence of benefit in individuals with and without type 2 DM, among those with ischaemic and non‐ischaemic heart failure aetiologies, and among those with an ejection fraction above or below the recruited population median 16 . Concomitant therapy, including angiotensin receptor–neprilysin inhibitor and MRA use, also did not modify these benefits when assessed in a series of post‐hoc subgroup analyses 35–37 . Dapagliflozin is now approved for the treatment of symptomatic chronic HFrEF 38…”
Section: Effects On Heart Failurementioning
confidence: 99%